Autotransplantation of the kidney in surgery of retroperitoneal sarcomas - R. I. Rasulov; A. A. Muratov; V. V. Dvornichenko; D. D. Morikov; Y. K. Batoroev; G. I. Songolov (Трансплантология (Москва), 2017)
The paper presents the analysis of 5 clinical cases that demonstrate the potential of using organ-saving technologies in surgery of locally advanced retroperitoneal sarcomas. The clinical example shows step by step the technique of organ-preserving surgical intervention: an extended tumour nephrectomy followed by the extracorporeal precise dissection of the kidney from the tumor bulk with inducing a reversible pharmaco-cold ischemia and the isolated kidney autotransplantation into a heterotopic position with regard to intraoperative rapid cytology monitoring results. The article describes the characteristics of anesthesia, the early postoperative period, subsequent rehabilitation, and prophylactic medical screening of this group of patients.